Conservation in the Nineteenth Century - Calvo Manuel, Ana (Ge-conservacion, 2014)
Reseña del libro: Conservation in the Nineteenth Century Archetype Publications in association with the National museetof Denmark and CATS (Centre for Art Technological Studies andConservation), Copenhagen. London, 2013.232 páginas, 220x300 mm. ISBN: 978-1-904982-91-3.